2022
DOI: 10.1177/15353702221113828
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic nomograms for newly diagnosed intrahepatic cholangiocarcinoma with brain metastasis: A population-based analysis

Abstract: Brain metastasis (BM) is one of the rare metastatic sites of intrahepatic cholangiocarcinoma (ICC). ICC with BM can seriously affect the quality of life of patients and lead to a poor prognosis. The aim of this study was to establish two nomograms to estimate the risk of BM in ICC patients and the prognosis of ICC patients with BM. Data on 19,166 individuals diagnosed with ICC were retrospectively collected from the Surveillance, Epidemiology, and End Results (SEER) database. Independent risk factors and progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In this study, we found that age, T-stage, N-stage and tumor size were strongly associated with distant metastasis in ICC, and the prediction model constructed based on the above risk factors was validated by ROC curves, calibration plots, DCA and validation cohort to show good accuracy, reliability and reproducibility of the model. Several previous studies have also suggested that age, histological grade, tumor size, lymph node metastasis and T-stage are independent risk factors for distant metastasis in ICC, and patient age is negatively associated with the risk of metastasis (12,13). In the model, T2 and T3 staging showed a higher risk of metastasis compared to T4, suggesting that vascular in ltration, multiple tumors, localized liver invasion or peritoneal penetration have a higher risk of metastasis than ductal in ltration in ICC.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we found that age, T-stage, N-stage and tumor size were strongly associated with distant metastasis in ICC, and the prediction model constructed based on the above risk factors was validated by ROC curves, calibration plots, DCA and validation cohort to show good accuracy, reliability and reproducibility of the model. Several previous studies have also suggested that age, histological grade, tumor size, lymph node metastasis and T-stage are independent risk factors for distant metastasis in ICC, and patient age is negatively associated with the risk of metastasis (12,13). In the model, T2 and T3 staging showed a higher risk of metastasis compared to T4, suggesting that vascular in ltration, multiple tumors, localized liver invasion or peritoneal penetration have a higher risk of metastasis than ductal in ltration in ICC.…”
Section: Discussionmentioning
confidence: 94%